Loncastuximab tesirine with rituximab in patients with relapsed or refractory follicular lymphoma: a single-centre, single-arm, phase 2 trial - Alderuccio, Juan Pablo; Alencar, Alvaro J; Schatz, Jonathan H; Kuker, Russ A; Pongas, Georgios; Reis, Isildinha M; Lekakis, Lazaros J; Spiegel, Jay Y; Sandoval-Sus, Jose; Beitinjaneh, Amer; Stanchina, Michele D; Trabolsi, Asaad; et al. (The Lancet. Haematology, 2025)
Preliminary data suggest promising activity of loncastuximab tesirine in follicular lymphoma, and synergistic activity between rituximab-induced cytotoxicity and loncastuximab tesirine. In this study, we evaluated loncastuximab tesirine combined with rituximab for second-line and later treatment of follicular lymphoma. We did a single-arm, investigator-initiated, phase 2 trial at Sylvester Comprehensive Cancer Center in Miami, FL, USA. We recruited patients aged 18 years or older with histologically confirmed relapsed or refractory follicular lymphoma (grade 1-3A) treated with one or more lines of therapy and presenting with progression or relapse of disease within 24 months (POD24) after the first line of treatment, one or more Groupe d'Etude des Lymphomes Folliculaires (GELF) criteria, or second relapse, and with an Eastern Cooperative Oncology Group performance status of 0-2. Intravenous loncastuximab tesirine was administered on day 1 of a 21-day cycle, at 0·15 mg/kg for two cycles, then 0·075 mg/kg thereafter. Intravenous rituximab was administered on day 1 of cycle 1, at 375 mg/m for four once-weekly doses, followed by one dose every 8 weeks on cycles 5, 6, and 7. At week 21, patients with a complete response discontinued loncastuximab tesirine and received two more doses of rituximab once every 8 weeks. Patients with a partial response at week 21 continued both agents for 18 more weeks. The primary endpoint was complete response rate at week 12 assessed by the Lugano 2014 classification in patients who had received at least three doses of loncastuximab tesirine. The safety analysis included all patients who received one or more doses of loncastuximab tesirine. The trial is registered with ClinicalTrials.gov, NCT04998669, and is ongoing (open to recruitment); the data cutoff for this analysis was Sept 13, 2024. Between Jan 28, 2022, and June 3, 2024, we enrolled 39 patients (median age 68 years [IQR 58-77]; 21 [54%] male patients and 18 [46%] female patients). All patients presented with one or more GELF criteria (n=36 [92%]) or POD24 after the first line of treatment (n=20 [51%]) at baseline. As of Sept 13, 2024, the median follow-up was 18·2 months (95% CI 12·0-19·3). Week 12 complete response rate was 67% (n=26 of 39). The most common grade 3 or worse treatment-emergent adverse events (TEAEs) were lymphopenia (eight [21%] of 39 patients) and neutropenia (five [13%] patients; one of whom had a serious grade 3 TEAE of febrile neutropenia that was considered to be related to study treatment). Generalised and peripheral oedema was predominantly grade 1-2 and all cases of oedema were treatable with diuretics. Serious TEAEs that were considered to be related to study drugs occurred in four (10%) of 39 patients. No fatal TEAEs occurred. Loncastuximab tesirine with rituximab showed clinically meaningful activity in relapsed or refractory follicular lymphoma, and had a manageable safety profile. ADC Therapeutics and Sylvester Comprehensive Cancer Center.